2019
DOI: 10.3390/metabo9040072
|View full text |Cite
|
Sign up to set email alerts
|

CFM-ID 3.0: Significantly Improved ESI-MS/MS Prediction and Compound Identification

Abstract: Metabolite identification for untargeted metabolomics is often hampered by the lack of experimentally collected reference spectra from tandem mass spectrometry (MS/MS). To circumvent this problem, Competitive Fragmentation Modeling-ID (CFM-ID) was developed to accurately predict electrospray ionization-MS/MS (ESI-MS/MS) spectra from chemical structures and to aid in compound identification via MS/MS spectral matching. While earlier versions of CFM-ID performed very well, CFM-ID’s performance for predicting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
197
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(199 citation statements)
references
References 41 publications
2
197
0
Order By: Relevance
“…Urine samples were further analyzed by LC‐MS/MS using a targeted approach with the same chromatographic conditions as described above and with three collision energies 10, 20, and 40 eV. MS/MS compound identification efforts included comparisons with authentic reference standards, fragmentation modeling using CFM ID, [ 46 ] and the HMDB [ 47 ] was used as a source. Metabolite Identification levels are reported according to Metabolomics standards initiative (MSI): with four levels of confidence in metabolite identification: Level I (Identified compounds); Level II (putatively annotated compounds); Level III (putatively characterized compound classes); Level IV (Unknowns).…”
Section: Methodsmentioning
confidence: 99%
“…Urine samples were further analyzed by LC‐MS/MS using a targeted approach with the same chromatographic conditions as described above and with three collision energies 10, 20, and 40 eV. MS/MS compound identification efforts included comparisons with authentic reference standards, fragmentation modeling using CFM ID, [ 46 ] and the HMDB [ 47 ] was used as a source. Metabolite Identification levels are reported according to Metabolomics standards initiative (MSI): with four levels of confidence in metabolite identification: Level I (Identified compounds); Level II (putatively annotated compounds); Level III (putatively characterized compound classes); Level IV (Unknowns).…”
Section: Methodsmentioning
confidence: 99%
“…Due to poor processing performance for large segmented molecules such as lipids, rulebased fragmentation was implemented in CFM-ID version 3.0 to predict the MS/MS spectra of 21 lipid classes, as well as a new scoring system and a chemical classification algorithm. These changes allow predicted ESI-MS/MS spectra of lipids to be obtained 200 times faster and ten times more accurately than when CFM-ID version 2.0 is used [110]. Thus, in-silico mass spectrometry is a fast-growing field, which should lead to advances in novel compound prediction and identification.…”
Section: Lc-ms Data Processingmentioning
confidence: 99%
“…This may have important consequences by increasing both the false annotation rate and the number of ‘unknown’ features arising from wrongly attributed signals. This is especially true when the annotation process is based on in silico modeling of fragmentation patterns, as are Sirius 12 , MS-FINDER 13 , MetFrag 14 or CFM-ID 15 , since tandem mass spectrometry (MS/MS) spectra are processed without taking into account feature relationships. Thus, most untargeted metabolomics studies focus on a subset of identified metabolites for which spectral data are easily accessible from public repositories or in-house DBs.…”
Section: Figurementioning
confidence: 99%